Agglomeration Economies and Productivity in Indian Industry - Lall, Somik; Shalizi, Zmarak; Deichmann, Uwe (World Bank, Washington, DC, 2014)
"New" economic geography theory, and the development of innovative methods of analysis have renewed interest in the location, and spatial concentration of economic activities. The authors examine the extent to which agglomeration economies contribute to economic productivity. They distinguish three sources of agglomeration economies: 1) At the firm level, from improved access to market centers. 2) At the industry level, from enhanced intra-industry linkages. 3) At the regional level, from inter-industry urbanization economies. The input demand framework they use in analysis, permits the production function to be estimated jointly with a set of cost shares, and, makes allowances for non-constant returns to scale, and for agglomeration economies to be factor-augmenting. They use firm-level data for standardized manufacturing in India, together with spatially detailed physio-geographic information that considers the availability, and quality of transport networks linking urban centers - thereby accounting for heterogeneity in the density of transport networks, between different parts of the country. The sources, and magnitudes of agglomeration vary considerably between industrial sectors. Their results indicate that access to markets, through improvements in inter-regional infrastructure, is an important determinant of firm-level productivity, whereas the benefits of locating in dense urban areas, do not appear to offset the associated costs. Improving the quality, and availability of transport infrastructure, linking smaller urban areas to the rest of the inter-regional network, would improve market access for manufacturing plants. It would also give standardized manufacturing activities a chance to move out of large, costly urban centers, to lower cost secondary centers.